Corporate hedging in the insurance industry: the use of financial derivatives by U.S. insurers - J. David Cummins; Richard D. Phillips; Stephen D. Smith (Federal Reserve Bank of Atlanta, 1996)
In this paper we investigate the extent to which insurance companies utilize financial derivatives contracts in the management of risks. The data set we employ allows us to observe the universe of individual insurer transactions for a class of contracts, namely, those normally through of as off-balance-sheet (OBS). We provide information on the number of insurers using various types of derivatives contracts and the volume of transactions in terms of notional amounts and the number of counterparties. Life insurers are most active in interest rate and foreign exchange derivatives, while property-casualty insurers tend to be active in trading equity option and foreign exchange contracts. Using a multivariate probit analysis, we explore the factors that potentially influence the existence of OBS activities. We also investigate questions relating to whether certain subsets of OBS transactions (e.g., exchange traded) are related to such things as interest rate risk measures, organizational form, and other characteristics that may discriminate between desired risk/return profiles across a cross-section of insurers. We find evidence consistent with the use of derivatives by insurers to hedge risks posed by guaranteed investment contracts (GICs), collateralized mortgage obligations (CMOs), and other sources of financial risk.
Keywords: 330; Corporations - Finance; Derivative securities; Insurance industry